The Believer's Confidence in a Faithful God : and the Needless Triumph of His Enemies Considered, in a Sermon, Preached on Lord's Day Morning, November 23, 1817, at Seven O'clock, at the Surrey Tabernacle - Church, J. (John) (Salt Lake City, UT : Project Gutenberg, 2018)
"The Believer's Confidence in a Faithful God" by J. Church is a sermon written in the early 19th century that reflects on the trials and confidence of believers in their God. This piece combines theological reflection with pastoral care, conveying the challenges faced by the faithful amidst persecution and the steadfast hope instilled through their faith. It addresses the struggles of believers and emphasizes the assurance that, despite adversities, God's presence and deliverance are guaranteed. In this sermon, Church uses the biblical text from Micah to frame his message of hope, expressing the idea that while believers may face falls into trouble or darkness, they can trust in God's faithfulness to lift them up and guide them through their difficulties. The sermon resonates with themes of resilience, divine providence, and the relationship between human suffering and spiritual growth. Throughout the text, Church encourages his listeners to remain steadfast in their faith, affirming that God$1 (Bs mercy and love will ultimately prevail over the challenges posed by enemies of the faith. The closing prayer is a heartfelt appeal to God for aid and resilience amidst trials, reinforcing the importance of reliance on divine support in such trying times. (This is an automatically generated summary.)s
Release date is 2018-12-26
Transcribed from the 1817 R. Thomas edition by David Price
Keywords: Sermons, English -- 19th century